DESIGN AND CONSTRUCTION OF LEAD ACID BATTERY LIFE CYCLE TESTER ACCORDING TO INDONESIAN NATIONAL STANDARD - Susanto Sigit Rahardi (Pusbindiklat - LIPI, 2012)
Lead acid battery life cycle tester has been designed and constructed at Electrical Laboratory in B4T. The system consists of voltage and current controller and digital system. The purpose of the system is to test life cyle of lead acid batteries to meet government regulation and laboratory requirements specified by Indonesian National Standard (SNI).